Longitudinal Trajectories of Hair Cortisol: Hypothalamic-Pituitary-Adrenal Axis Dysfunction in Early Childhood - Rovnaghi, Cynthia R.; Rigdon, Joseph; Roué, Jean-Michel; Ruiz, Monica O.; Carrion, Victor G.; Anand, Kanwaljeet J. S. (Frontiers in Pediatrics, 2021)
The objective of this study was to examine if longitudinal trajectories of hair cortisol concentrations (HCC) measured in at least two of three yearly time points can identify 1-3 year old children at high risk for altered hypothalamic-pituitary-adrenal (HPA)-axis function due to early life stress (ELS). HCC was measured (N=575) in 265 children using a validated enzyme-linked immunosorbent assay sampled at years 1, 2, and 3 (n=45); 1 and 2 (n=98); 1 and 3 (n=27); 2 and 3 (n=95). Log-transformed HCC values were partitioned using latent class mixed models (LCMM) to minimize the Bayesian Information Criterion. Multivariable linear mixed effects models for ln-HCC as a function of fixed effects for age in months and random effects for participants (to account for repeated measures) were generated to identify the factors associated with class membership. Children in Class 1 (n=69; 9% Black) evidenced declining ln-HCC across early childhood, whereas Class 2 members (n=196; 43% Black) showed mixed trajectories. LCMM with only Class 2 members revealed Class 2A (n=17, 82% Black) with sustained high ln-HCC and Class 2B (n=179, 40% Blacks) with mixed ln-HCC profiles. Another LCMM limited to only Class 2B members revealed Class 2B1 (n=65, 57% Black) with declining ln-HCC values (at higher ranges than Class 1), and Class 2B2 (n=113, 30% Black) with sustained high ln-HCC values. Class 1 may represent hair cortisol trajectories associated with adaptive HPA-axis profiles, whereas 2A, 2B1, and 2B2 may represent allostatic load with dysregulated profiles of HPA-axis function in response to varying exposures to ELS. Sequential longitudinal hair cortisol measurements revealed the allostatic load associated with ELS and the potential for developing maladaptive or dysregulated HPA-axis function in early childhood.